The budget and the cost price of the european parliament ? - Matthijs, Herman (Advances in Social Sciences Research Journal, 2019)
Every five years ( 2014, 2019 ) the electorate of the European Union (E.U.) member states has the opportunity of electing a new European Parliament. This Parliament is the legislative body of the E.U. and the voters from the 27 member states, after the Brexit, will elect 705 seats in May 2019. The financing of the European Parliament is a part of the general budget of the European Union. The own income and all the expenditures of the European Parliament are a complete part of this general budget of the Union. This article examines the following items in further detail: - how has the appropriation for the European Parliament evolved since 2003? - what is the budget of the European Parliament spent on? - is it possible to compare the costs of the European Parliament to those of other Parliaments? - how have the costs of each MEP evolved?